A 3D Polymeric Platform for Photonic Quantum Technologies. Issue 7 (1st June 2020) - Colautti, Maja; Lombardi, Pietro; Trapuzzano, Marco; Piccioli, Francesco S.; Pazzagli, Sofia; Tiribilli, Bruno; Nocentini, Sara; Cataliotti, Francesco S.; Wiersma, Diederik S.; Toninelli, Costanza
Abstract: The successful development of future photonic quantum technologies will much depend on the possibility of realizing robust and scalable nanophotonic devices. These should include quantum emitters like on‐demand single‐photon sources and non‐linear elements, provided their transition linewidth is broadened only by spontaneous emission. However, conventional strategies to on‐chip integration, based on lithographic processes in semiconductors, are typically detrimental to the coherence properties of the emitter. Moreover, such approaches are difficult to scale and bear limitations in terms of geometries. Here an alternative platform is discussed, based on molecules that preserve near‐Fourier‐limited fluorescence even when embedded in polymeric photonic structures. 3D patterns are achieved via direct laser writing around selected molecular emitters, with a fast, inexpensive, and scalable fabrication process. By using an integrated polymeric design, detected photon counts of about 2.4 Mcps from a single cold molecule are reported. The proposed technology will allow for competitive organic quantum devices, including integrated multi‐photon interferometers, arrays of indistinguishable single‐photon sources, and hybrid electro‐optical nanophotonic chips. Abstract : A major challenge in quantum technologies is the on‐chip integration of quantum emitters in a way that can be scaled up and preserves the emitter coherence properties. In the unconventional platform here introduced, molecules are selectively embedded in 3D polymeric structures, obtained by direct laser writing. Near‐Fourier‐limited fluorescence, single‐photon emission and enhanced collection efficiency are reported for the integrated molecules.